EBV Exploits RNA m6A Modification to Promote Cell Survival and Progeny Virus Production During Lytic Cycle - Yanagi, Yusuke; Watanabe, Takahiro; Hara, Yuya; Sato, Yoshitaka; Kimura, Hiroshi; Murata, Takayuki (Frontiers in Microbiology, 2022)
N6-methyladenosine (m6A) mediates various biological processes by affecting RNA stability, splicing, and translational efficiency. The roles of m6A modification in Epstein-Barr virus (EBV) infection in the lytic phase are unclear. Here, knockout of the m6A methyltransferase, N6-methyladenosine methyltransferase-like 3 (METTL3), or inhibition of methylation by DAA or UZH1a decreased the expression of viral lytic proteins and reduced progeny virion production. Interestingly, cell growth and viability were decreased by induction of the lytic cycle in METTL3-knockout or inhibitor-treated cells. Apoptosis was induced in those conditions possibly because of a decreased level of the anti-apoptotic viral protein, BHRF1. Therefore, m6A shows potential as a target of lytic induction therapy for EBV-associated cancers, including Burkitt lymphoma.